2016
DOI: 10.3747/pdi.2016.00017
|View full text |Cite
|
Sign up to set email alerts
|

Do Dialysis Decision AIDS Improve Treatment Decision-Making?

Abstract: Several studies report people with advanced kidney disease are dissatisfied with the amount and type of information they receive about dialysis treatment options. 3 A systematic review of patients' perspectives about treatment option information found 10 of 18 studies in which patients and family members felt they had

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Many patients are reluctant to transfer to HD, even when clinically indicated, because they perceive that such a transfer would adversely affect their quality of life. A proper presentation of, and possible use of decision aids about different renal replacement therapies, including home HD and the option of conservative care, from the start of treatment onward (integrated care) could potentially reduce disappointment when a transfer is needed (3)(4)(5).…”
mentioning
confidence: 99%
“…Many patients are reluctant to transfer to HD, even when clinically indicated, because they perceive that such a transfer would adversely affect their quality of life. A proper presentation of, and possible use of decision aids about different renal replacement therapies, including home HD and the option of conservative care, from the start of treatment onward (integrated care) could potentially reduce disappointment when a transfer is needed (3)(4)(5).…”
mentioning
confidence: 99%
“…Within this nested set of effects, patient misunderstandings do arise, and in the course of prognostic discussions, clinicians should try to undo misunderstandings. 61 Studies across multiple contexts have shown well-designed material can help patients make higher quality kidney replacement therapy treatment decisions 62 ; however, little is known on the best way to aid patients in untangling potentially misconstrued health beliefs arising from educational websites of dialysis organizations which may also have a marketing component. 63 This is important given that surrogate information seekers already frequently use the internet, 64 and internet use is increasing among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study conducted in Germany in 2016, more than one-fourth of the HD patient stated that dialysis modality selection was made by a nephrologist without asking for their decisions and opinions [ 43 ]. A systematic review study showed that out of 18 studies, in 10 studies, patients and their families believed that they did not receive sufficient SDM-related information [ 62 ]. In a study in the United Kingdom, Durand et al [ 63 ] found that more than half of patients with chronic kidney disease were unaware of all RRTs as a potential treatment and were reluctant to talk with their healthcare professionals about it.…”
Section: Discussionmentioning
confidence: 99%